MODEL PENINGKATAN BRAND LOYALTY BERDASARKAN KUALITAS PELAYANAN ISLAM DAN ATRIBUT PRODUK ISLAM MELALUI BRAND TRUST - fidyah yuli ernawati; Lisa Zahratul Adni; Asyhari Asyhari (Sekolah Tinggi Ilmu Ekonomi Semarang, 2022)
The main objective of this study is to investigate and examine the effect of Islamic service quality and Islamic product attributes on brand loyalty through brand trust, and propose an empirical model to investigate this correlation. A total of 100 respondents from BMT/KSPPS NU Sejahtera customers in the city of Semarang filled out a questionnaire about brand loyalty, Islamic service quality, Islamic product attributes and brand trust. The results of the structural equation based on PLS SEM confirms that providing Islamic service quality can directly and significantly affect brand loyalty; while the attributes of Islamic products have no significant effect on brand loyalty. So there is a need for more improvements to the attributes of Islamic products in order to increase brand loyalty.